Rice Policy in Java from Traditional Kingdoms to Dutch Colonial Time - Wasino , Wasino; Hartatik , Endah Sri (KnE Social Sciences, 2019)
Rice is main food for Indonesian people nowadays. Rice is consumed by all people in Indonesian society and planted in several places in Indonesia. Based on the historical data, rice was dominantly planted in Java, Due to the importance of rice, any political rulerinIndonesiapaidattentiontoricetostabilizehisauthority.Thisarticlewillconduct historical analysis about the policy of rice from traditional ruler in Java Dutch Colonial. For analyzed it used historical method by using historical sources which searched fromNationalLibraryJakarta,NationalarchiveJakarta,andKITLcollectionfromLeiden University Library, and Mangkunegaran Palace Library. The research ﬁnding show that rice was the main food from Traditional Javanese kingdom to Dutch Colonial time. The Ruler take special policy to made rice availability for people prosperity. Keywords: rice, prosperity, traditional, historical sources, ruler, availability